Negative electrode material for zinc-manganese battery and preparation method of negative electrode material

By using zinc-manganese batteries with zinc-containing organic gel electrolytes, the problems of mercury pollution and high gas volume of traditional electrolytes are solved, and higher discharge capacity and battery safety are achieved.

CN119812338APending Publication Date: 2025-04-11JIAXING HENGWEI BATTERY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510006783.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In existing zinc-manganese batteries, mercury as an additive to the negative electrode material has problems of environmental pollution and health risks. At the same time, traditional potassium hydroxide electrolytes lead to high gas extraction volume and insufficient battery safety.

Method used

Using an electrolyte system without water, a new zinc paste is prepared by adding zinc trifluoromethanesulfonate-containing organic gel electrolyte to prepare a negative electrode material for zinc-manganese batteries, effectively inhibiting the corrosion of zinc powder, reducing the gas discharge volume, and increasing the discharge capacity.

Benefits of technology

It achieves more efficient ion conduction, reduces electrode polarization, improves discharge capacity, and reduces gas discharge volume, enhancing the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a negative electrode material for a zinc-manganese battery and a preparation method of the negative electrode material. The negative electrode material for the zinc-manganese battery comprises 60-70 wt% of zinc powder, 2-6 wt% of an adhesive and 25-35 wt% of organic gel electrolyte containing zinc trifluoromethanesulfonate. The preparation method comprises the following steps: mixing the zinc powder, the adhesive and the organic gel electrolyte containing the zinc trifluoromethanesulfonate, and stirring and mixing for 30-60 minutes under the conditions of 20-100 rpm, 25-35 DEG C and vacuum to obtain the negative electrode material for the zinc-manganese battery. Compared with the prior art, the prepared negative electrode material for the zinc-manganese battery can effectively inhibit corrosion of zinc powder and reduce the gas evolution amount, and has relatively high discharge capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc-manganese batteries, and in particular to a negative electrode material for zinc-manganese batteries and a preparation method thereof. Background Art

[0002] In alkaline zinc-manganese batteries, the negative electrode material plays a key role. The commonly used negative electrode material is zinc powder, which is in powder form, which is different from the zinc tube negative electrode in acid zinc-manganese batteries. In addition, there is also amalgamated zinc powder negative electrode. Amalgamation is the process of mixing mercury and zinc powder to form an alloy. This operation is of great significance. It can increase the hydrogen overvoltage of zinc powder in alkaline electrolyte, thereby effectively inhibiting the generation of hydrogen, reducing the self-discharge of the battery, and making the discharge performance of the alkaline zinc-manganese battery more stable, ensuring its stable and long-lasting power supply in various electrical appliances. However, there are many disadvantages to introducing mercury. On the one hand, mercury is a highly toxic heavy metal. If it is not handled properly during the battery production process, it is easy to leak. After the used batteries are discarded, mercury will seep out and pollute the soil and water, and then cause harm to animals and plants in the ecosystem through biological enrichment in the food chain. On the other hand, after mercury enters the human body, it will accumulate in organs such as the kidneys and liver, damaging organ function, especially the nervous system, affecting cognitive, sensory and motor functions. The harm to children and pregnant women is more serious, and may lead to problems such as intellectual retardation in children, posing serious health risks.

[0003] CN115863556A discloses a preparation process of a titanium dioxide nanoparticle-coated zinc powder negative electrode material, first dissolving a titanate coupling agent in a solvent, sequentially adding a phosphate surfactant and anhydrous ethanol to obtain a mixed solution A, adding zinc powder to obtain a mixed solution B, then slowly dripping ascorbic acid under stirring at 45°C to 65°C, continuing to stir and react to obtain a mixed solution C, and finally filtering and drying to obtain the negative electrode material. It has obvious advantages, can inhibit zinc powder self-corrosion and passivation, reduce battery gas evolution, improve zinc powder utilization, increase battery capacity, extend storage time and enhance battery safety.

[0004] CN117913354A discloses a method for preparing a zinc ion battery-related material and a battery. The prepared gel electrolyte uses polyvinyl alcohol as a framework, introduces nanocellulose and reduced graphene oxide, and is formed by physical and chemical cross-linking. When preparing the gel electrolyte, PVA is first dissolved in a solvent, graphene oxide is added, stirred at high temperature for 2 hours, and then CNF is added, and finally dried. For the preparation of semi-solid batteries, manganese sulfate and ammonium persulfate are first dissolved in a solvent, and a sample is obtained by a one-step hydrothermal method. After washing and drying, a defective positive electrode material MnO2 is made, and a positive electrode sheet is made with a stainless steel mesh as a current collector, and a zinc sheet is used as a negative electrode, and assembled into a flexible battery test. The invention effectively solves the problems of electrolyte leakage and zinc negative electrode dendrites, and has good application and development potential in the field of zinc ion batteries. Summary of the invention

[0005] The present invention proposes a new negative electrode material for zinc-manganese batteries. A non-aqueous electrolyte system is adopted. By adding an organic gel electrolyte containing zinc trifluoromethanesulfonate, a new zinc paste is successfully prepared. The zinc paste can effectively inhibit the corrosion of zinc powder, reduce the amount of gas evolution, and has a higher discharge capacity.

[0006] The specific technical solutions are as follows:

[0007] A negative electrode material for a zinc-manganese battery comprises the following components: 60-70wt% of zinc powder, 2-6wt% of a binder, and 25-35wt% of an organic gel electrolyte containing zinc trifluoromethanesulfonate. The preparation method comprises the following steps: mixing the zinc powder, the binder, and the organic gel electrolyte containing zinc trifluoromethanesulfonate, and stirring and mixing for 30-60min at 20-100rpm, 25-35°C, and vacuum to obtain the negative electrode material for the zinc-manganese battery.

[0008] Further preferably, the negative electrode material for zinc-manganese battery is composed of the following components: 65wt% zinc powder, 3wt% binder, and 32wt% organic gel electrolyte containing zinc trifluoromethanesulfonate.

[0009] Preferably, the adhesive is any one of polyacrylic acid, sodium carboxymethyl cellulose, polytetrafluoroethylene emulsion, and styrene-butadiene rubber emulsion.

[0010] Organic gel electrolyte, also known as polymer gel electrolyte, is a special material between solid and liquid, with a three-dimensional network structure. It has significant advantages, high safety, not easy to leak, can avoid short circuit, corrosion and other problems; can inhibit the growth of zinc dendrites, its network structure helps zinc ions to deposit evenly, reduce the risk of internal short circuit, and extend the cycle life; can maintain ionic conductivity in a wide temperature range.

[0011] Preferably, the preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate is as follows: in an inert atmosphere, slowly adding zinc trifluoromethanesulfonate powder to a solvent, and continuously stirring at 20-100 rpm for 20-40 min until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; slowly adding a gelling agent and continuing to stir at 20-100 rpm for 1-4 h to allow the gelling agent to be fully dissolved and dispersed in the solution; thus, the organic gel electrolyte containing zinc trifluoromethanesulfonate is obtained.

[0012] Further preferably, the preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate is: in an inert atmosphere, 10-30g of zinc trifluoromethanesulfonate powder is slowly added to 50-150mL of solvent, and stirring is continued at 20-100rpm for 20-40min until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; 5-15g of gelling agent is slowly added and stirring is continued at 20-100rpm for 1-4h to fully dissolve and disperse the gelling agent in the solution; the organic gel electrolyte containing zinc trifluoromethanesulfonate is obtained.

[0013] The gelling agent is any one of polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polyacrylonitrile, and polymethyl methacrylate. Most preferably, the gelling agent is polyvinylidene fluoride-hexafluoropropylene.

[0014] The solvent is at least one of ethylene carbonate, propylene carbonate, N-methylpyrrolidone, tetrahydrofuran and dimethyl carbonate.

[0015] Beneficial effects of the present invention:

[0016] Compared with the prior art, the zinc-manganese battery negative electrode material of the present invention uses an organic gel electrolyte containing zinc trifluoromethanesulfonate, which has a better ion conduction channel than the traditional potassium hydroxide electrolyte, and can make ions migrate more efficiently during the electrode reaction process. Moreover, the organic gel electrolyte containing zinc trifluoromethanesulfonate has better compatibility with other electrode materials, helps to form a more stable reaction interface on the electrode surface, reduces electrode polarization, and achieves a higher discharge capacity. DETAILED DESCRIPTION

[0017] A method for preparing a negative electrode material for a zinc-manganese battery is as follows:

[0018] Raw material ratio: 60-70wt% zinc powder, 2-6wt% adhesive, 25-35wt% organic gel electrolyte containing zinc trifluoromethanesulfonate;

[0019] Preparation of zinc paste: zinc powder, a binder, and an organic gel electrolyte containing zinc trifluoromethanesulfonate are mixed, and stirred for 30-60 minutes at 20-100 rpm, 25-35° C., and vacuum to obtain the negative electrode material for the zinc-manganese battery.

[0020] The adhesive is any one of polyacrylic acid, sodium carboxymethyl cellulose, polytetrafluoroethylene emulsion and styrene-butadiene rubber emulsion.

[0021] The preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate is as follows: in an inert atmosphere, zinc trifluoromethanesulfonate powder is slowly added to a solvent, and the mixture is continuously stirred at 20-100 rpm for 20-40 min until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; a gelling agent is slowly added and the mixture is continuously stirred at 20-100 rpm for 1-4 h to fully dissolve and disperse the gelling agent in the solution; and the organic gel electrolyte containing zinc trifluoromethanesulfonate is obtained.

[0022] The gelling agent is any one of polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polyacrylonitrile and polymethyl methacrylate.

[0023] The parameters and sources of some raw materials in the examples are as follows:

[0024] Sodium carboxymethyl cellulose, degree of substitution (DS) 0.80-1.00.

[0025] Polyvinylidene fluoride-hexafluoropropylene, brand: Kynar Flex 2801-00, from Arkema.

[0026] Polyethylene oxide, viscosity 65-115cps, sourced from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0027] Polyacrylonitrile, average molecular weight 50,000, was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0028] Polymethyl methacrylate nitrile, brand: CM-205, from Chi Mei Industrial.

[0029] Example 1

[0030] A method for preparing a negative electrode material for a zinc-manganese battery is as follows:

[0031] Raw material ratio: 65wt% zinc powder, 3wt% sodium carboxymethyl cellulose, 32wt% organic gel electrolyte containing zinc trifluoromethanesulfonate;

[0032] Preparation of zinc paste: zinc powder, sodium carboxymethyl cellulose and an organic gel electrolyte containing zinc trifluoromethanesulfonate are mixed, and stirred for 50 minutes at 50 rpm, 30° C. and vacuum to obtain the negative electrode material for the zinc-manganese battery.

[0033] The preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate comprises the following steps: in an inert atmosphere, 50 mL of ethylene carbonate and 40 mL of propylene carbonate are stirred and mixed uniformly; 18 g of zinc trifluoromethanesulfonate powder is slowly added, and stirring is continued at 100 rpm for 30 min until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; 10 g of polyvinylidene fluoride-hexafluoropropylene is slowly added, and stirring is continued at 100 rpm for 2 h to fully dissolve and disperse the gelling agent in the solution; and the organic gel electrolyte containing zinc trifluoromethanesulfonate is obtained.

[0034] Comparative Example 1

[0035] A method for preparing a negative electrode material for a zinc-manganese battery is as follows:

[0036] Raw material ratio: zinc powder 65wt%, sodium carboxymethyl cellulose 3wt%, electrolyte 32wt%;

[0037] Preparation of zinc paste: zinc powder, sodium carboxymethyl cellulose and electrolyte were mixed, and stirred at 50 rpm and 30° C. for 50 min to obtain the negative electrode material for the zinc-manganese battery.

[0038] The electrolyte is obtained by uniformly mixing 35 g of potassium hydroxide, 65 g of water, and 4.1 g of zinc oxide.

[0039] Example 2

[0040] A method for preparing a negative electrode material for a zinc-manganese battery is as follows:

[0041] Raw material ratio: 65wt% zinc powder, 3wt% sodium carboxymethyl cellulose, 32wt% organic gel electrolyte containing zinc trifluoromethanesulfonate;

[0042] Preparation of zinc paste: zinc powder, sodium carboxymethyl cellulose and an organic gel electrolyte containing zinc trifluoromethanesulfonate are mixed, and stirred for 50 minutes at 50 rpm, 30° C. and vacuum to obtain the negative electrode material for the zinc-manganese battery.

[0043] The preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate is as follows: in an inert atmosphere, 50 mL of ethylene carbonate and 40 mL of propylene carbonate are stirred and mixed uniformly; 18 g of zinc trifluoromethanesulfonate powder is slowly added, and stirring is continued at 100 rpm for 30 minutes until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; 10 g of polyethylene oxide is slowly added and stirring is continued at 100 rpm for 2 hours to fully dissolve and disperse the gelling agent in the solution; and the organic gel electrolyte containing zinc trifluoromethanesulfonate is obtained.

[0044] Example 3

[0045] A method for preparing a negative electrode material for a zinc-manganese battery is as follows:

[0046] Raw material ratio: 65wt% zinc powder, 3wt% sodium carboxymethyl cellulose, 32wt% organic gel electrolyte containing zinc trifluoromethanesulfonate;

[0047] Preparation of zinc paste: zinc powder, sodium carboxymethyl cellulose and an organic gel electrolyte containing zinc trifluoromethanesulfonate are mixed, and stirred for 50 minutes at 50 rpm, 30° C. and vacuum to obtain the negative electrode material for the zinc-manganese battery.

[0048] The preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate comprises the following steps: in an inert atmosphere, stirring and mixing 90 mL of N-methylpyrrolidone uniformly; slowly adding 18 g of zinc trifluoromethanesulfonate powder, and continuously stirring at 100 rpm for 30 min, until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; slowly adding 10 g of polyacrylonitrile, and continuously stirring at 100 rpm for 2 h, so that the gelling agent is fully dissolved and dispersed in the solution, thereby obtaining the organic gel electrolyte containing zinc trifluoromethanesulfonate.

[0049] Example 4

[0050] A method for preparing a negative electrode material for a zinc-manganese battery is as follows:

[0051] Raw material ratio: 65wt% zinc powder, 3wt% sodium carboxymethyl cellulose, 32wt% organic gel electrolyte containing zinc trifluoromethanesulfonate;

[0052] Preparation of zinc paste: zinc powder, sodium carboxymethyl cellulose and an organic gel electrolyte containing zinc trifluoromethanesulfonate are mixed, and stirred for 50 minutes at 50 rpm, 30° C. and vacuum to obtain the negative electrode material for the zinc-manganese battery.

[0053] The preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate is as follows: in an inert atmosphere, 50 mL of tetrahydrofuran and 40 mL of dimethyl carbonate are stirred and mixed uniformly; 18 g of zinc trifluoromethanesulfonate powder is slowly added, and stirring is continued at 100 rpm for 30 minutes until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; 10 g of polymethyl methacrylate is slowly added and stirring is continued at 100 rpm for 2 hours to fully dissolve and disperse the gelling agent in the solution, so as to obtain the organic gel electrolyte containing zinc trifluoromethanesulfonate.

[0054] Application Examples 1-4

[0055] The assembly of LR6 alkaline zinc-manganese battery is carried out by conventional methods:

[0056] 1. Production of positive electrode ring

[0057] Material preparation: 500 g electrolytic manganese dioxide, 40 g expanded graphite, 2.5 g sodium carboxymethyl cellulose and 25 g organic gel electrolyte containing zinc trifluoromethanesulfonate (organic gel electrolyte containing zinc trifluoromethanesulfonate in Example 1-4);

[0058] Production process: First, electrolytic manganese dioxide, expanded graphite and sodium carboxymethyl cellulose are quickly stirred evenly, then an organic gel electrolyte containing zinc trifluoromethanesulfonate is added and stirred for 10 minutes, and then rolled into sheets and crushed into granules; pressed into positive electrode rings, each positive electrode ring is 14.10mm high, 13.66mm in outer diameter, and weighs about 3.75g; 3 positive electrode rings constitute the positive electrode material;

[0059] 2. Preparation of zinc paste: negative electrode material for zinc-manganese battery of Examples 1-4

[0060] 3. Battery Assembly

[0061] Materials preparation: three positive electrode rings, an LR6 nickel-plated steel shell (the inner layer of which is coated with a graphite conductive film), a VLM2523-110 diaphragm paper tube, 1.4 g of an organic gel electrolyte containing zinc trifluoromethanesulfonate (the organic gel electrolyte containing zinc trifluoromethanesulfonate in Example 1-4), 6.3 g of zinc paste (the negative electrode material for the zinc-manganese battery in Example 1-4), as well as a sealing ring, a negative electrode cover and a copper nail;

[0062] Assembly steps: Press three positive electrode rings into the LR6 nickel-plated steel shell, put the diaphragm paper tube along the inner diameter of the positive electrode ring, paste a layer of 1.4g of organic gel electrolyte containing zinc trifluoromethanesulfonate into the diaphragm paper tube of each battery, then put 6.3g of zinc paste into the diaphragm paper tube, crimp it on the machine and apply sealant; combine the sealing ring and the negative electrode cover into the battery negative electrode cap, weld it with the copper nail as the negative electrode collector, and insert the negative electrode zinc paste, and finally seal the battery into shape.

[0063] Application Example 5

[0064] The assembly of LR6 alkaline zinc-manganese battery is carried out by conventional methods:

[0065] 1. Production of positive electrode ring

[0066] Material preparation: 500 g electrolytic manganese dioxide, 40 g expanded graphite, 2.5 g sodium carboxymethyl cellulose and 25 g electrolyte (the electrolyte in Control Example 1);

[0067] Production process: First, electrolytic manganese dioxide, expanded graphite and sodium carboxymethyl cellulose are quickly stirred evenly, then the electrolyte is added and stirred for 10 minutes, and then rolled into sheets and crushed into granules; pressed into positive electrode rings, each positive electrode ring is 14.10mm high, the outer diameter of the ring is 13.66mm, and each positive electrode ring weighs about 3.75g; 3 positive electrode rings constitute the positive electrode material;

[0068] 2. Preparation of zinc paste: negative electrode material for zinc-manganese battery of comparative example 1

[0069] 3. Battery Assembly

[0070] Materials preparation: three positive electrode rings, an LR6 nickel-plated steel shell (the inner layer of which is coated with a graphite conductive film), a VLM2523-110 diaphragm paper tube, 1.4g electrolyte (the electrolyte in Comparative Example 1), 6.3g zinc paste (the negative electrode material for the zinc-manganese battery in Comparative Example 1), as well as a sealing ring, a negative electrode cover and a copper nail;

[0071] Assembly steps: Press three positive electrode rings into the LR6 nickel-plated steel shell, place the diaphragm paper tube along the inner diameter of the positive electrode ring, inject 1.4g of electrolyte into the diaphragm paper tube of each battery, then put 6.3g of zinc paste into the diaphragm paper tube, crimp it on the machine and apply sealant; combine the sealing ring and the negative electrode cover into the battery negative electrode cap, weld it with the copper nail as the negative electrode collector, and insert the negative electrode zinc paste, finally seal the battery into shape.

[0072] The sources of some raw materials in the application examples are as follows:

[0073] Electrolytic manganese dioxide, manganese dioxide content 92.33%, particle size 500 mesh, from Hunan Qingchong New Materials Co., Ltd.;

[0074] Expanded graphite, model KP32, expansion rate 200-400mL / g, from Qingdao Baichuan Graphite Co., Ltd.;

[0075] Sodium carboxymethyl cellulose, degree of substitution (DS) 0.80-1.00.

[0076] Test Example 1

[0077] The constant resistance discharge test is to connect a fixed resistor in the circuit. As the battery discharges, the voltage division of the battery internal resistance and the load resistance changes continuously, causing the current to change accordingly. This test method focuses more on simulating the situation where the battery is connected to a fixed resistive load (such as a small electronic device) in actual applications, and observes the voltage change and capacity output of the battery under such actual load conditions. During the entire discharge process of the battery, the shape of the voltage change curve over time, especially the length and stability of the discharge platform. Compared with the constant current discharge test, the constant resistance discharge test is closer to the actual application scenario, because many electronic devices are equivalent to a fixed resistance load for the battery, so it can well evaluate the performance of the battery in actual use.

[0078] Specific test method: Place the assembled battery in the application example under standard environmental conditions (temperature 20±2℃, humidity 45-55%) for 4 hours; use the DM-2000 battery automatic discharge detection system to perform a constant resistance discharge test. The resistance value of the electronic load is set to 10Ω, and the termination voltage is 0.9V. The test results are shown in Table 1.

[0079] Table 1

[0080] Capacity mAh Example 1 2676 Comparative Example 1 2176 Example 2 2438 Example 3 2382 Example 4 2345

[0081] As can be seen from the above table, the negative electrode material (zinc paste) for zinc-manganese batteries of Examples 1-4 has a higher discharge capacity than the negative electrode material (zinc paste) for zinc-manganese batteries of Comparative Document 1. The organic gel electrolyte containing zinc trifluoromethanesulfonate has a better ion conduction channel than the traditional potassium hydroxide electrolyte, which enables ions to migrate more efficiently during the electrode reaction. Moreover, the organic gel electrolyte containing zinc trifluoromethanesulfonate has better compatibility with other electrode materials, which helps to form a more stable reaction interface on the electrode surface and reduce electrode polarization.

[0082] Embodiments 1-4 all use organic gel electrolytes containing zinc trifluoromethanesulfonate, but the discharge capacity of the negative electrode material (zinc paste) for zinc-manganese batteries of embodiment 1 is significantly higher than that of the negative electrode material (zinc paste) for zinc-manganese batteries of embodiment 2-4. Experiments have shown that different gelling agents with different solvents have different effects on zinc trifluoromethanesulfonate in organic gel electrolytes containing zinc trifluoromethanesulfonate. The use of polyvinylidene fluoride-hexafluoropropylene with solvents ethylene carbonate and propylene carbonate and containing zinc trifluoromethanesulfonate can provide a more suitable transmission environment for zinc ions, which is conducive to the migration of ions during battery discharge, thereby helping to improve the discharge capacity of the battery. In the process of gel electrolyte, polyvinylidene fluoride-hexafluoropropylene with solvents ethylene carbonate and propylene carbonate and containing zinc trifluoromethanesulfonate constructs a three-dimensional network structure that is more conducive to ion transmission, so that the electrolyte can allow zinc ions to move more smoothly therein while maintaining a certain shape and stability, which helps to improve the discharge performance of the battery.

[0083] Test Example 2

[0084] The method for determining the amount of gas evolution is as follows:

[0085] Weigh 45g of zinc paste (negative electrode material for zinc-manganese battery of Examples 1-4 and Comparative Example 1) and place it in a gas collecting bottle, then fill it with liquid paraffin, plug it with a rubber stopper with a measuring tube, and the bottom of the measuring tube is 2cm away from the zinc paste at the bottom of the bottle to form a completely closed environment. Keep it constant temperature for 1 hour under the condition of a 60°C water bath, record the time at this moment and the scale value corresponding to the liquid concave liquid surface, and record it as V0. Then keep it constant temperature at 60°C for 7 days, read the height of the liquid concave liquid surface, and record it as V1. The volume of hydrogen precipitated by the zinc paste is the difference between V1 and V0. The gas evolution amount is in mL / 7 days, and its calculation formula is: the gas evolution amount of zinc paste (mL / 7 days) = V1-V0, wherein V0 represents the reading seven days ago (in mL), and V1 represents the reading seven days later (in mL). The above test is repeated 3 times, and the average value is finally taken as the result. Note: The zinc paste, the negative electrode material for zinc-manganese battery of the present invention, is stirred in vacuum during the preparation process, that is, it is always under negative pressure and basically does not contain bubbles.

[0086] Table 2

[0087] Gas evolution volume (mL) Example 1 0.01 Comparative Example 1 0.37 Example 2 0.05 Example 3 0.04 Example 4 0.04

[0088] As can be seen from the above table, the amount of gas evolution of the negative electrode materials for zinc-manganese batteries in Examples 1-4 is much lower than that of the negative electrode materials for zinc-manganese batteries in Comparative Example 1. The reason is that the zinc paste used in the negative electrode materials for zinc-manganese batteries in Examples 1-4 is an organic gel electrolyte containing zinc trifluoromethanesulfonate. The structure of this organic gel electrolyte is relatively stable, and it can inhibit the self-discharge reaction of zinc to a certain extent. The structure of the gel may limit the movement speed of ions in the electrolyte, making it difficult for side reactions between zinc and the electrolyte (such as hydrogen evolution reaction) to occur. The potassium hydroxide electrolyte commonly used in the prior art has a strong alkalinity, and zinc is more active in this strong alkaline electrolyte and is prone to self-discharge reaction. Zinc reacts with water in the electrolyte to produce hydrogen, resulting in a large amount of gas evolution. Furthermore, the organic gel electrolyte has a gel-like physical state, which can be better adsorbed on the surface of zinc powder to form a relatively stable protective film. This protective film can prevent excessive contact between the electrolyte and zinc powder, reduce the chemical reaction caused by direct contact, and thus reduce the amount of gas evolution. Conventional potassium hydroxide electrolyte is in liquid state and can fully contact with zinc powder, which makes the reaction between zinc powder and electrolyte easier to proceed and increases the possibility of gas evolution.

[0089] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A negative electrode material for a zinc-manganese battery, characterized in that: The invention comprises the following components: 60-70 wt % of zinc powder, 2-6 wt % of a binder and 25-35 wt % of an organic gel electrolyte containing zinc trifluoromethanesulfonate.

2. The negative electrode material for zinc-manganese battery according to claim 1, characterized in that: The invention is composed of the following components: 65 wt % of zinc powder, 3 wt % of a binder and 32 wt % of an organic gel electrolyte containing zinc trifluoromethanesulfonate.

3. The negative electrode material for zinc-manganese battery according to claim 1, characterized in that: The adhesive is any one of polyacrylic acid, sodium carboxymethyl cellulose, polytetrafluoroethylene emulsion and styrene-butadiene rubber emulsion.

4. The negative electrode material for zinc-manganese battery according to claim 1, characterized in that: The preparation method of the organic gel electrolyte containing zinc trifluoromethanesulfonate is as follows: in an inert atmosphere, zinc trifluoromethanesulfonate powder is slowly added to a solvent, and the mixture is continuously stirred at 20-100 rpm for 20-40 min until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; a gelling agent is slowly added and the mixture is continuously stirred at 20-100 rpm for 1-4 h to fully dissolve and disperse the gelling agent in the solution; and the organic gel electrolyte containing zinc trifluoromethanesulfonate is obtained.

5. The negative electrode material for zinc-manganese battery according to claim 4, characterized in that: The preparation method of the zinc trifluoromethanesulfonate-containing organic gel electrolyte is as follows: in an inert atmosphere, 10-30 g of zinc trifluoromethanesulfonate powder is slowly added to 50-150 mL of solvent, and the mixture is continuously stirred at 20-100 rpm for 20-40 min until the zinc trifluoromethanesulfonate is completely dissolved to form a uniform solution; 5-15 g of gelling agent is slowly added and the mixture is continuously stirred at 20-100 rpm for 1-4 h to fully dissolve and disperse the gelling agent in the solution; and the zinc trifluoromethanesulfonate-containing organic gel electrolyte is obtained.

6. The negative electrode material for zinc-manganese battery according to claim 4 or 5, characterized in that: The gelling agent is any one of polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polyacrylonitrile and polymethyl methacrylate.

7. The negative electrode material for zinc-manganese battery according to claim 6, characterized in that: The gelling agent is polyvinylidene fluoride-hexafluoropropylene.

8. The negative electrode material for zinc-manganese battery according to claim 4 or 5, characterized in that: The solvent is at least one of ethylene carbonate, propylene carbonate, N-methylpyrrolidone, tetrahydrofuran and dimethyl carbonate.

9. The method for preparing the negative electrode material for zinc-manganese battery according to any one of claims 1 to 8, characterized in that: Zinc powder, a binder and an organic gel electrolyte containing zinc trifluoromethanesulfonate are mixed, and stirred and mixed for 30-60 minutes at 20-100 rpm, 25-35° C. and vacuum to obtain the negative electrode material for the zinc-manganese battery.

Citation Information

Patent Citations

  • Preparation and application of gel electrolyte for wide-temperature zinc-manganese battery

    CN117913354A